Patterned Arrays of Supramolecular Microcapsules. (30th March 2018) - Zhang, Jing; Liu, Ji; Yu, Ziyi; Chen, Su; Scherman, Oren A.; Abell, Chris
Abstract: Micropatterning of hydrogel has brought innovative outcomes in fundamental and applied material sciences. Previous approaches have mainly been dedicated to fabricate arrays of bulk hydrogel beads, which have inherent challenges including loading ability, scalability, specificity, and versatility. Here, a methodology is presented to create hollow microcapsule arrays from sessile microdroplets. The difference in wettability between hydrophilic and hydrophobic surfaces enables self‐partitioning of liquid into microdroplet arrays, serving as microreservoirs to load complementarily functionalized host–guest polymers, cucurbit[8]uril‐threaded highly branched polyrotaxanes (HBP‐CB[8]) and naphthyl‐functionalized hydroxyethyl cellulose (HEC‐Np). The interfacial dynamic complexation between positively charged HBP‐CB[8] and HEC‐Np occurs in the presence of negatively charged surfactants, resulting in condensed supramolecular hydrogel skins. The hydrogel microcapsules are uniform in size and are developed to encapsulate target cargos in a robust and well‐defined manner. Moreover, the microcapsule substrates are further used for surface enhanced Raman spectroscopy sensing upon loading of gold nanoparticles. This facile assembly of microcapsule arrays has potential applications in controlled cargo delivery, bio‐sensing, high‐throughput analysis, and sorting. Abstract : Formation of patterns of supramolecular microcapsules from cucurbit[8]uril‐threaded highly branched polyrotaxane (HBP‐CB[8]) and naphthyl‐functionalized hydroxyethyl cellulose HEC (HEC‐Np), through the wettability‐mediated printing process. The interfacial dynamic complexation between positively charged HBP‐CB[8] and HEC‐Np occurs under the assistance of negatively charged surfactants, resulting in condensed yet dynamic supramolecular microcapsule skin.